10 days Chiam See Tong, the SPP and GE 2011 - Ng, Norman (Pasir, 2012)
This book of black and white photographs provides a record of the Singapore People Party's (SPP) GE 2011 campaign, published by sponsorship and donations from many supporters, to commemorate the SPP's involvement in a momentous period in Singapore's political history.